Annual Plan 2004-2005 (Executive Summary) Government of Nagaland - Planning Commission (Planning Commission, 2004)
Despite various problems and impediments an analysis of the progress of implementation plan programmes during the first two Annual Plans, 2002 - 2003 and 2003 - 2004 has indicated a very satisfactory realization of physical targets in most of the core, major and priority sectors. The reform processes initiated by the State in different sectors continue to give positive impact on the development perspectives of the State. During the 1st two Annual Plans, several major projects have been completed and commissioned, notable among them are, 24 MW Likimro Hydel project, 1st Phase of Indira Gandhi Stadium, Police Head Quarter Office Building, Inter-State Bus Terminus under North Eastern Council programme, Communitisation of Public Institutions and Services etc.
Government of Nagaland, Planning and Co-ordination Department
Planning and Co-ordination Department Government of Nagaland